Protease accessibility laddering: a proteomic tool for probing protein structure - Dokudovskaya, Svetlana; Devos, Damien (Structure, 2006)
Summary Limited proteolysis is widely used in biochemical and crystallographic studies to determine domain organization, folding properties, and ligand binding activities of proteins. The method has limitations, however, due to the difficulties in obtaining sufficient amounts of correctly folded proteins and in interpreting the results of the proteolysis. A new limited proteolysis method, named protease accessibility laddering (PAL), avoids these complications. In PAL, tagged proteins are purified on magnetic beads in their natively folded state. While attached to the beads, proteins are probed with proteases. Proteolytic fragments are eluted and detected by immunoblotting with antibodies against the tag (e.g., Protein A, GFP, and 6×His). PAL readily detects domain boundaries and flexible loops within proteins. A combination of PAL and comparative protein structure modeling allows characterization of previously unknown structures (e.g., Sec31, a component of the COPII coated vesicle). PAL's high throughput should greatly facilitate structural genomic and proteomic studies.